Menggunakan Model Kepala Bernomor Struktur Dalam Meningkatkan Hasil Belajar Matematika - Rusmi Manurung (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Classroom action research generally aims to improve the quality of learning for grade VI students of SDN 018477 BP. Mandoge. specifically aims to: 1. Efforts to improve student achievement; 2. Describe the management of Mathematics learning; 3. Using the Head Numbered Method, Material Structure Simplifies and Sorting Fractions. This classroom action research was conducted in 2 cycles, each cycle consisting of planning, acting, observing and reflecting. Classroom action research was carried out in class VI SDN 018477 BP. Mandoge, amounting to 26 students. The subjects of this study were the sixth grade mathematics teachers and the sixth grade students of SDN 018477 BP. Mandoge, data were collected through observation, interviews, tests, and study documentation. Keywords: head number together, fraction  Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas VI SDN 018477 BP. Mandoge. secara khusus bertujuan untuk : 1. Upaya Meningkatkan Prestasi Belajar Siswa; 2. Mendeskripsikan pengelolaan pembelajaran Matematika ; 3. Menggunakan Model Kepala Bernomor Struktur Materi Menyederhanakan dan Mengurutkan Pecahan. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas dilaksanakan dikelas VI SDN 018477 BP. Mandoge yang berjumlah 26 orang siswa. Subjek penelitian ini adalah guru Matematika kelas VI dan siswa kelas VI SDN 018477 BP. Mandoge, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Kata Kunci :   kepala bernomor struktur, pecahan.